The Principle of Equality of Arms in Light of the Decisions of the Constitutional Court and European Court of Human Rights - Akif Yıldırım; Ayhan Kılıç (Ceza Hukuku ve Kriminoloji Dergisi)
The principle of equality of arms proposes that a fair balance be provided between the parties to a proceeding and that equality must be ensured between the parties regarding their rights and obligations during the course of the proceeding. This balance must be maintained through all stages of the proceeding. In light of the judgments of the European Court of Human Rights and the Constitutional Court, this study examines issues related to the equality of arms, which is a constitutional safeguard within the ambit of the right to a fair trial. Additionally, the study submits solution suggestions regarding these matters. The foundational principle of equality of arms, its conceptual framework, and its elements are explained in achieving the objectives of this study. Further, the different practical versions of the principle, as it relates to the right to a fair trial, will be addressed.